Academic supervision in improving teachers’ professional competency in paramount school palembang - Kgs Rachmad Dody Fadillah; Happy Fitria; Alfroki Martha (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
The research problem is about the implementation of academic supervision held by the Paramount Primary School Principal which considered unoptimal. The aim of this study are: (1) Explaining the elements that being focused in academic supervision of Paramount Primary School. (2) Explaining the strategy of the Principal in improving teacher’s professional competency. (3) Explaining the implementation of academic supervision held by the Principal (4). Analyzing the implementation of academic supervision held by the Principal in pandemic time. This reseach is a qualitatif descritive reseach, data collection technique used is participatory observation, in-depth interviews, and documentation.The subject in this study are the principal, teachers and students. The results of this study are: (1) the elements supervised, (2) Strategy applied in improving the professional competence of teachers and (3) The follow up conducted by the principal after the academic supervision activity.